Hospital infections - medical, legal, economic and ethical issues - Brodowicz-Król, Magdalena; Trojanowska, Alina; Korżyńska-Piętas, Magdalena; Grzegorczyk, Michał; Medak, Edyta (Journal of Education, Health and Sport, 2018)
The aim is to present factors that threaten the health and life of the patient staying in a hospital setting. Objects and tools that, as a result of human error, penetrate the patient’s tissues and body cavities, cause a high risk of infection. These include surgical instruments, gynecological instruments, needles, syringes, catheters, and dressings. The requirements for the cleanliness of equipment, objects and tools are manifold, depending on the degree of risk of infection. The sterility of the equipment and tools is maintained thanks to the proper handling of the material before sterilization, properly carried out sterilization process, compliance with transport and storage rules. Analysis of deactivation conditions and assessment of its effectiveness provides a guarantee of prevention of nosocomial infections [4].